Single radio UHPLC analysis for the quality control of technetium-99m radiolabelled radiopharmaceuticals. (October 2021) - Schmitt, Camille; Fouque, Julien; Huguet, Samuel; Da Costa Branquinho, Emilie; Blondeel, Sandy; Rezai, Keyvan; Madar, Olivier
Abstract: The radiochemical purity (RCP) determination of radiopharmaceuticals is routinely done with radio-thin layer chromatography (r-TLC). These methods are usually transposed and adjusted from the summary product characteristics without any analytical validation. The r-TLC method is simple but manually-performed steps could lead to RCP misinterpretation. To increase the sensitivity, radio ultra-high performance liquid chromatography (r-UHPLC) can be used. In this study, an r-UHPLC method had been validated and compared to the r-TLC method. Hydrolyzed-reduced technetium had also been studied. Highlights: Technetium-99m is frequently used to prepare radiopharmaceuticals (RP). The radiochemical purity (RCP) is evaluated by thin layer chromatography (TLC). Ultra-high performance liquid chromatography (UHPLC) increases the sensitivity. A single UHPLC method allows the RCP determination of 4 different 99m Tc-RP. The UHPLC method is robust, reproducible, automated and safer than the TLC method.